Centennial Memory of the Arctic Ocean for Future Arctic Climate Recovery in Response to a Carbon Dioxide Removal - Ji‐Hoon Oh; Soon‐Il An; Jongsoo Shin; Jong‐Seong Kug (Earth's Future, 2022)
Abstract Under the ongoing and potential risks from anthropogenic warming, net negative carbon dioxide (CO2) emissions are inevitable to stabilize or recover the Earth's climate. It is important not only to understand climate irreversibility in response to CO2 removal but also to understand how fast each component of the climate system will recover to its original state. Based on idealized CO2 ramp‐up and ‐down ensemble simulations, here we show that the initial buoyancy states of the Arctic Ocean, such as upper ocean salinity and density, are vital to determining how fast Arctic and global mean temperatures will recover on a centennial time scale. The denser initial Arctic oceanic condition is linked to faster recovery of the Atlantic meridional overturning circulation (AMOC) in the ramp‐down period, which is further accelerated by strong positive AMOC‐salt‐advection feedback. Faster AMOC recovery can delay Arctic temperature recovery by transporting warmer water into the northern subpolar Atlantic during the ramp‐down period. In addition, denser Arctic water enhances vertical mixing, which also results in delayed Arctic cooling under a strong vertical temperature gradient in the subpolar‐to‐polar Atlantic. Our findings suggest that the Arctic's initial states have a centennial memory for the future Arctic and global climate changes.